2014
DOI: 10.1101/gad.236729.113
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of tRNA transcription with export at nuclear pore complexes in budding yeast

Abstract: tRNAs are encoded by RNA polymerase III-transcribed genes that reside at seemingly random intervals along the chromosomes of budding yeast. Existing evidence suggests that the genes congregate together at the nucleolus and/or centromeres. In this study, we re-examined spatial and temporal aspects of tRNA gene (tDNA) expression. We show that tDNA transcription fluctuates during cell cycle progression. In M phase, when tRNA synthesis peaks, tDNAs localize at nuclear pore complexes (NPCs). Docking of a tDNA requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 61 publications
3
64
0
Order By: Relevance
“…Likewise, we did not detect any change in the formation of the extranucleolar body upon the loss of either Nup2 or Nup60 (Fig. 4B), two nucleoporins known to be involved in the correct tethering of tRNA genes to NPCs in early mitosis (Chen and Gartenberg 2014). Similar data were obtained in cells deficient in nucleoporins (Nup42, Nup100, Nup116, and Nup159) that directly interact with Crm1 (Fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Likewise, we did not detect any change in the formation of the extranucleolar body upon the loss of either Nup2 or Nup60 (Fig. 4B), two nucleoporins known to be involved in the correct tethering of tRNA genes to NPCs in early mitosis (Chen and Gartenberg 2014). Similar data were obtained in cells deficient in nucleoporins (Nup42, Nup100, Nup116, and Nup159) that directly interact with Crm1 (Fig.…”
Section: Resultssupporting
confidence: 74%
“…The potential presence of mechanisms to accelerate the delivery of ribosomes to the growing bud also remains unexplored. Interestingly, tRNA production is subject to spatial regulation during the cell cycle because tRNA genes become tethered to nuclear pore complexes (NPCs) in early mitosis through a Los1 exportin-mediated process (Chen and Gartenberg 2014). This mechanism is thought to expedite the export and accumulation of tRNAs in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Pol II must be delivered to specific genes, and the nuclear positioning of a given Pol II-transcribed gene can be important for its expression (7). Finally, Pol III-transcribed tRNA genes occupy distinct subnuclear positions; both the nucleous and nuclear pores are considered in budding yeast (8,9). It is also possible that a nuclear/nucleous structure exists, which functions as a platform to localize these assembly events.…”
mentioning
confidence: 99%
“…Although the nucleolus is located on the nuclear envelope in yeast, genes could transiently relocalize to other NPC. In addition to gene gating for RNAP II promoters such as the LTRs, transcriptionally active tDNAs have been shown to localize to NPC (30). Consistent with the latter possibility, chromatin conformation capture analysis of yeast chromosomal DNA indicated that a subpopulation of tDNAs are not associated with rDNA (31).…”
Section: Ty3 Expression Mating Control Of Ty3 Expressionmentioning
confidence: 58%
“…RNAP III genes undergo specific types of epigenetic modifications and bind chromatin remodelers and condensins (179)(180)(181)(182)(183)(184)(185)(186)(187)(188)(189)(190). In addition to possible differences in chromatin context, tDNAs also act as replication fork barriers (191), and subpopulations localize to the nucleolus (31,192) and nuclear pores (30). Overall, it seems that we are just beginning to learn about the dynamic activities of RNAP IIItranscribed genes.…”
Section: Genomewide Identification Of Ty3 Targets and Rnap III Factormentioning
confidence: 99%